PLAYING GAMES IN RUSSIAN AS A FOREIGN LANGUAGE LESSONS - Ramazanova Roza Abilovna (Modern American Journals, 2025)
The article contains recommendations for the teacher on conducting role-playing games in Russian language lessons as a foreign language, as well as examples of games that activate students' speech within specific topics. Using such work methods contributes to the intellectual, emotional, and moral development of the individual.
Keywords: Role-playing games, Russian as a foreign language, speech interaction, game and speech activity.